THE ROLE OF THE TEACHER IN DEVELOPING VOCAL AND CHORAL SKILLS IN STUDENTS (Web of Teachers: Inderscience Research, 2024)
This article analyzes the role of the teacher in the development of vocal and choral skills in students in secondary schools. The article discusses the importance of vocal and choral performance in music education, the role of the teacher in the educational process and methodological approaches. The responsibility of the teacher is of great importance in developing the voice of students, forming musical intuition and improving their group performance skills. This article shows that vocal and choral art can stimulate the creative activity of students, help their personal and social development.